Pengaruh NPL, LDR, Dan CAR Terhadap Penyaluran Kredit Pada Perbankan Di Indonesia (Literature Review Manajemen Keuangan) - Angrawit Kusumawardani (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Previous research or relevant research is very important for scientific journal literature research. This research reviews the influence of NPL, LDR and CAR on credit distribution to banks in Indonesia. The results of this literature review research are: 1) Nonperforming loans (NPL) have a negative effect on credit distribution; 2) Loan to deposit ratio (LDR) has a positive effect on credit distribution; 3) Capital adequacy ratio (CAR) has a negative effect on credit distribution.